Egy hátrányos helyzetű település egyedi lehetőségei és törekvései a helyi gazdaságfejlesztés tekintetében - Eskulics, György; Gelencsér, Zsófia; Horváth, Szilveszter; Siklósi, Rozália; Szuromi, Orsolya (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
This study is about Rimóc, a Hungarian village with 1 800 residents, where the local economic development (LED) is a main ambition, because in the concept of demographic and employment relations Rimóc is considered an underprivileged settlement. The research was carried out by a 5 manned team, where using the method of deep interviews, short interviews and a focus group interview, made with the help of locals, revealed some difficulties. These are the lack of cooperation between the locals, ethnic problems, lack of assets and motivation, which are preventing the process of the LED. Overcoming these problems can become the key of the future and sustainable development of the settlements. Since Hungary has many villages which also try to reach the state of self-sufficiency, in the case of Rimóc the tendency is similar, where the municipality, mainly the mayor, of the village initiated the begining of such processes in food supply and power supply.